Electrical and dielectrical properties of composites based on (Ag₁₋ₓCuₓ)₇GeS₅I mixed crystals - Izai, V.Yu.; Studenyak, V.I.; Pogodin, A.I.; Studenyak, I.P.; Rajnak, M.; Kurimsky, J.; Timko, M.; Kopcansky, P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2018)
Polymer composites were prepared from (Ag₁₋ₓCuₓ)₇GeS₅I mixed crystals grown using the Bridgman–Stockbarger method. The impedance measurements were performed at room temperature in the frequency range 10⁻³–2·10⁶ Hz. The frequency dependences of electrical conductivity and dielectric permittivity for composites based on (Ag₁₋ₓCuₓ)₇GeS₅I mixed crystals were obtained. The Nyquist plots for (Ag₁₋ₓCuₓ)₇GeS₅I-based composite have been analyzed. The influence of cation Ag→Cu substitution on the electrical conductivity of composites based on (Ag₁₋ₓCuₓ)₇GeS₅I mixed crystals has been studied.